Early detection of vertebral artery dissection. Issue 1 (28th November 2018) - MacArthur, Alice Morag; Mehdi, Syed
Abstract : A 36-year-old female patient presented to hospital with a 1-week history of occipital headache. It was sudden onset following a fall into a swimming pool. Examination was unremarkable. CT angiogram brain scan showed right vertebral artery dissection with a 1 cm dissection flap and a 3 mm left middle cerebral artery aneurysm. She was discharged on aspirin, with outpatient neurology clinic follow-up.